New record of a Poecilimon species (Orthoptera: Tettigoniidae: Phaneropterinae; Barbitistini) from China - Wu, Chao; Liu, Chunxiang (Zootaxa, 2019)
Although in “Fauna Sinica Insecta” 247 species of Phaneropterinae are recorded for China, there is not a single record of a species from the tribe Barbitistini. Herein, we newly record a small-sized and short-winged species of this tribe belonging to the genus Poecilimon (Fischer, 1853). We identified the species as Poecilimon intermedius (Fieber, 1853) which was collected in the Xinjiang Uygur Autonomous region, China. The records of the interesting species extend its distributional range in Asia. Detailed citations, description and necessary illustrations are provided.